CREATIVE ECONOMY ON E-WAROENG KUBE - Erti Dinihayati; Yanti Purwanti (SAMPURASUN, 2020)
ABSTRACT Creative economy is the creation of added value (economic, social, cultural, environment) based on ideas that are born from the creativity of human resources (creative people) and based on the use of knowledge, including cultural and technological heritage. Creativity is not limited to works based on art and culture, but can also be based on science and technology, engineering and telecommunications. There are 3 main things that are the basis of the creative economy, including creativity, innovation and discovery. E-warong KUBE is a community empowerment program in the economic field and through the Prosperous Indonesia Community Card issued by BNI is expected to empower the poor to achieve a prosperous society. This program facilitates economic transactions for residents receiving the Family Hope Program (PKH). The amount of non-cash food aid is Rp. 110,000.0 / KPM / month, the assistance cannot be collected in cash, and can only be done with rice and / or eggs in e-warong. If assistance is not spent in that month, the value of assistance will still be stored and accumulated in the Food Aid Electronic Account. The aim of KUBE e-waroeng can be achieved through increasing the ability or empowerment of families and communities, as well as increasing community access to social resources in the community so as to foster creativity, innovation and discoveries that can make e-waroeng have economic value to realize development a sustainable economy based on creativity. Keyword : creative economy, KUBE e-waroeng, creativity